2018
DOI: 10.3389/fpls.2018.00502
|View full text |Cite
|
Sign up to set email alerts
|

Aldaulactone – An Original Phytotoxic Secondary Metabolite Involved in the Aggressiveness of Alternaria dauci on Carrot

Abstract: Qualitative plant resistance mechanisms and pathogen virulence have been extensively studied since the formulation of the gene-for-gene hypothesis. The mechanisms involved in the quantitative traits of aggressiveness and plant partial resistance are less well-known. Nevertheless, they are prevalent in most plant-necrotrophic pathogen interactions, including the Daucus carota–Alternaria dauci interaction. Phytotoxic metabolite production by the pathogen plays a key role in aggressiveness in these interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 84 publications
2
23
0
Order By: Relevance
“…It was also indicated that aldaulactone was involved in both fungal pathogenicity and plant resistance mechanisms. In phytotoxicity, aldaulactone was toxic to carrot cells, inducing a delay in embryonic development and a decrease in cell viability [142]. The biological function and biosynthetic pathway of aldaulactone has not yet been defined.…”
Section: Macrolidesmentioning
confidence: 99%
“…It was also indicated that aldaulactone was involved in both fungal pathogenicity and plant resistance mechanisms. In phytotoxicity, aldaulactone was toxic to carrot cells, inducing a delay in embryonic development and a decrease in cell viability [142]. The biological function and biosynthetic pathway of aldaulactone has not yet been defined.…”
Section: Macrolidesmentioning
confidence: 99%
“…On the contrary, in vitro carrot cell toxicity of aldaulactone was pointed out at concentrations observed in A. dauci cultures. In an original way, this toxicity is negatively correlated with carrot cell resistance 39 . Interestingly, it is only the second evidence, with SS-toxin in the Stemphylium solani - Allium sativum pathosystem, of a link between fungal SMs and partial resistance 37 , 39 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, numerous phytopathogenic Alternaria species produce HSTs that cause high specificity for their host 8 . So far at least seven phytotoxins have been isolated and characterized from A. dauci cultures: zinniol, alternariol, alternariol monomethyl-ether, α -acetylorcinol, p -hydroxybenzoic acid and aldaulactone 39 43 . To our knowledge, little is known about their biosynthetic pathways, except for the alternariol biosynthetic cluster that was recently predicted by sequence homology 44 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations